Nanosecond pulse effectively ablated hepatocellular carcinoma with alterations in the gut microbiome and serum metabolites - Zou, Yawen; Sun, Ying; Chen, Xinhua; Hong, Liangjie; Dong, Gang; Bai, Xiwen; Wang, Haiyu; Rao, Benchen; Ren, Zhigang; Yu, Zujiang (Frontiers in Pharmacology, 2023)
Background: Hepatocellular carcinoma (HCC) was the third leading cause of cancer-related death in the world. Nanosecond pulsed electric fields (nsPEFs) have emerged as a new treatment for cancer. This study aims to identify the effectiveness of nsPEFs for HCC and analyze the alterations of the gut microbiome and serum metabonomics after ablation. Methods: C57BL/6 mice were randomly divided into three groups: healthy control mice (n=10), HCC mice (n=10), and nsPEFs-treated HCC mice (n=23). Hep1-6 cell lines was used to establish HCC model in situ. Histopathological staining was performed on tumor tissues. Gut microbiome was analyzed by 16S rRNA sequencing. Serum metabolites by liquid chromatography-mass spectrometry (LC-MS) metabolomic analysis. Using Spearmans correlation analysis to analyze the correlation between gut microbiome and serum metabonomics. Results: Fluorescence image showed that nsPEFs was significantly effective. Histopathological staining identified nuclear pyknosis and cells necrosis in the nsPEFs group. The expression of CD34, PCNA, and VEGF decreased significantly in the nsPEFs group. Compared with normal mice, the gut microbiome diversity of HCC mice was increased. Eight genera including Alistipes and Muribaculaceae were enriched in the HCC group. Inversely, these genera increased in the nsPEFs group. LC-MS analysis confirmed that there were significantly differences in serum metabolism among the three groups. Correlation analysis showed crucial relationships between gut microbiome and serum metabolites that involved in nsPEFs ablation of HCC. Conclusion: As a new minimally invasive treatment for tumor ablation, nsPEFs has an excellent ablation effect. The alterations in the gut microbiome and serum metabolites may participate in the prognosis of HCC ablation.